Long-term follow-up of vitrectomy, with or without 360° encircling buckle, for rhegmatogenous retinal detachment due to inferior retinal breaks - Ghoraba, Hamouda Hamdy (Clin Ophthalmol, 2016)
OBJECTIVE: The aim of this study was to report and compare the anatomic and functional results of primary vitrectomy with and without 360° encircling scleral buckle (SB) for the treatment of rhegmatogenous retinal detachment (RRD) due to inferior retinal break(s). BACKGROUND: A variety of options, including SB, pars plana vitrectomy (PPV) with or without SB, and pneumatic retinopexy have been described as methods to repair RRDs. The use of additional SB with vitrectomy for RRD associated with inferior breaks has been a recent controversy after the introduction of transconjunctival cannula systems. PATIENTS AND METHODS: A retrospective, interventional, comparative case study was performed. In this study, we reviewed 105 consecutive patients who underwent vitrectomy for primary RRD with inferior retinal break(s) at the vitreoretinal center, performed by a single surgeon. Ninety four patients (94 eyes) were followed up for at least 4 months after silicon oil removal (SOR), and were analyzed. They were divided into two groups: group I included 50 patients who underwent PPV alone + silicon oil (SO); and group II included 44 patients who underwent PPV with 360° SB + SO. The essential parameters were single-operation success rate (SOSR) before SOR, incidence of retinal redetachment after SOR, and final visual acuity. RESULTS: SOSR was obtained in 89 eyes (47 [94%] in group I and 42 [95.5%] in group II). From overall 59 phakic retinal detachments (RDs), SOSR was obtained in 56 eyes (30 in group I [93.8%] and 26 in group II [96.3%]) while from overall 35 aphakic or pseudophakic RDs, SOSR was obtained in 33 eyes (17 in group I [94.4%] and 16 in group II [94.1%]). Retinal redetachments after SOR occurred in three patients in group I and two patients in group II. Visual acuity improvement was greater in group I than in group II before SOR. CONCLUSION: Both surgical procedures had similar reattachment rates. The addition of 360° SB to PPV + SO might not have additional benefits in patients with RD due to inferior retinal break.